Edukasi Penggunaan Obat Rasional di Kampung Tok Kassim, Changlun, Kedah - Syafitri, Yeshaira Zahra Shabira; Widayanti, Ari; Prastiwi, Rini; Amirullah, Gufron (Universitas Negeri Gorontalo, 2024)
Rational drug use is a crucial aspect of medication management that requires a thorough understanding to ensure that treatment regimens are appropriately tailored to meet the individual needs of patients, administered within the correct timeframes, and remain affordable. When drug use is irrational, it can result in serious health consequences such as organ damage, the development of drug resistance, and in severe cases, even death. To address this, it is vital to enhance awareness about the importance of rational drug use and its benefits. In Tok Kassim Village, several health services were provided, including comprehensive blood sugar, blood pressure, and cholesterol checks, as well as interactive discussions and a question-and-answer session with the local residents. These activities revealed that the average villager uses medication to manage cholesterol levels, hypertension, and blood sugar. The interactive discussions and question-and-answer sessions were particularly effective and smooth because the villagers demonstrated a good understanding of the principles of rational drug use, highlighting the positive impact of the educational efforts in reinforcing the significance of proper medication management.